A comparison on PSO variants in calculating HEPWM switching angles for a cascaded H-bridge multilevel inverter - Norkharziana, Mohd Nayan; Naziha, Ahmad Azli, Dr.; Sharin, Md Ayob, Dr. (Springer Science+Business Media, LLC, 2013)
Link to publisher's homepage at http://link.springer.com/